Effects of STC on postoperative recovery of disturbance of consciousness in traumatic multiple intracranial hematoma patients. Issue 12 (26th March 2021) - Wang, Dan; Zhou, Zhulin; Zhang, Bingjie; Zhang, Bo; Yang, Hongfa
Abstract: Objective: The study explored the therapeutic value of standard trauma craniectomy (STC) for the treatment of traumatic multiple intracranial hematoma. Methods: Clinical data of traumatic multiple intracranial hematoma patients who underwent surgical treatment in 2014 and 2015 were collected. The STC group and a control group according to the surgical mode, 48 and 30 cases were randomly selected from each group, respectively. Statistical analysis was performed on the change in the Glasgow coma scale (GCS) score from before the operation to 1 day, 1 week and 1 month postoperatively through repeated analysis of variance and Wilcoxon rank-sum analysis. Results: Significant differences in the GCS were observed at different time points for the two operative modes ( P  < .01), and an interaction was observed between time and treatment groups ( P  < .05). The rates of change of the GCS score for the two surgical modes were most obviously different at 3 days and 1 week postoperatively ( P  ⩽ .001, P  < .01). No statistically significant differences were observed in the rates of change of the GCS at 1 month postoperatively ( P  > .05). Conclusions: Compared to conventional craniotomy, STC has obvious effects on the recovery after disturbance of consciousness at 1 week postoperatively but does not result in a significant improvement in recovery at 1 month postoperatively.